Pengaruh Penambahan Fly Ash Terhadap Nilai Koefisien Permeabilitas Tanah Lempung Organik - Fauzi, Muhammad Muis; Indriani, Andi Marini; Utomo, Gunaedy (Journal of Applied Civil Engineering and Infrastructure Technology, 2025)
The role of soil is very crucial and is always closely related to infrastructure development. This is because soil functions as the basis for building construction, serving to receive and support the structural loads placed on it. In high rainfall weather conditions, the surface of the slope is susceptible to landslides. Landslides occur due to excessive water infiltration, causing the soil to become weak and collapse. To prevent landslides, efforts need to be made to reduce soil infiltration or permeability. The purpose of this study was to determine the characteristics of the addition of Fly Ash to the permeability of organic clay soil and to determine the optimum composition of the addition of Fly Ash to reduce the permeability coefficient value. The addition of variations in the percentage of Fly Ash was 8%, 16%, and 24% with a curing period of 3 days, 14 days, and 28 days. The test results obtained with the addition of 24% Fly Ash resulted in a decrease in the permeability coefficient value of 84.08% against untreated soil. It can be concluded that the use of Fly Ash can be used as a soil stabilization material, especially in permeability testing.